2019
DOI: 10.1016/j.infpip.2019.100027
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Multidrug- and Pandrug- Resistant Pseudomonas aeruginosa from Five Hospitals in Qatar

Abstract: Summary Background A global rise in multidrug-resistant (MDR) nosocomial infections has led to a significant increase in morbidity and mortality. MDR Gram-negative bacteria (GNB) are recognised for rapidly developing drug resistance. Despite Pseudomonas aeruginosa being the second most common GNB isolated from healthcare associated infections, the magnitude of MDR P. aeruginosa (MDR-PA) has not been evaluated in Qatar. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…A total of fifteen articles published in English, between the period of 2010 and 2020 were identified and reviewed, nine articles were prospective studies (Siddiqua et al, 2018;Farooq et al, 2019;Ahmadi et al, 2016;Rustini et al, 2017;Senthamarai, 2014;Farhan et al, 2019;Ahmed et al, 2019;Al-Marzoqi and Al Taee, 2013;Khan and Faiz, 2016), four were descriptive cross sectional studies (Pokharel et al, 2019;Karami et al, 2020;Mahfoud et al, 2015;Alhusseini et al, 2019), one systemic review and meta-analysis study (Acar et al, 2019) and one retrospective study (Al-Tawfiq et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of fifteen articles published in English, between the period of 2010 and 2020 were identified and reviewed, nine articles were prospective studies (Siddiqua et al, 2018;Farooq et al, 2019;Ahmadi et al, 2016;Rustini et al, 2017;Senthamarai, 2014;Farhan et al, 2019;Ahmed et al, 2019;Al-Marzoqi and Al Taee, 2013;Khan and Faiz, 2016), four were descriptive cross sectional studies (Pokharel et al, 2019;Karami et al, 2020;Mahfoud et al, 2015;Alhusseini et al, 2019), one systemic review and meta-analysis study (Acar et al, 2019) and one retrospective study (Al-Tawfiq et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This study focused mainly on the resistance pattern of P. aeruginosa against different drugs in different countries. It was observed that the highest resistance rate was against Cefuroxime in Bangladesh (Siddiqua et al, 2018), Ceftriaxone in Indonesia (Rustini et al, 2017), Imipenem in Pakistan (Farooq et al, 2019), Ampicillin (Ahmadi et al, 2016) and Ticarcillin/Clavulanic Acid (Karami et al, 2020) in Iran, Co-Trimoxazole in Nepal (Pokharel et al, 2019), Ceftazidime in India and Egypt (Senthamarai, 2014;Farhan et al, 2019), Cefepime in Qatar (Ahmed et al, 2019), Amoxicillin/Clavulanic Acid in Syria (Mahfoud et al, 2015), Penicillin and Amoxicillin/Clavulanic Acid in Iraq (Alhusseini et al, 2019), Aztreonam in Turkey (Acar et al, 2019) and Meropenem (Khan and Faiz, 2016), Ciprofloxacin followed by Meropenem and Imipenem (Al-Tawfiq et al, 2020) then both Carbapenems (Al-Tawfiq et al, 2020) in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations